A flow cytometry‐based assay to determine the phagocytic activity of both clinical and nonclinical antibody samples against Chlamydia trachomatis. Issue 5 (7th March 2018) - Grasse, Marco; Rosenkrands, Ida; Olsen, Anja; Follmann, Frank; Dietrich, Jes
Abstract: Globally, an estimated 131 million new cases of chlamydial infection occur annually. Chlamydia trachomatis infection can cause permanent damage to the fallopian tubes in woman, resulting in infertility and a risk of ectopic pregnancy. There is a great need for a vaccine against Chlamydia trachomatis and as a result there is a need for assays to evaluate functional immune responses for use in future clinical trials and epidemiological studies. Antibodies play a crucial role in the defense against infection and can be protective by several functions, including phagocytosis and neutralization. Vaccine development could greatly benefit from a method to measure functional C. trachomatis ‐specific antibodies in a large number of samples. In the current in vitro antibody protection assays, which measure the capacity of antibodies to facilitate phagocytic uptake of C. trachomatis, the phagocytosed bacteria have to be counted manually. This is both labor demanding, time consuming, and it prevents high‐throughput usage of this method. In this study, we, therefore, developed a simple and rapid flow cytometry based assay to measure the capacity of antibodies to mediate Fc‐receptor dependent phagocytosis. This method is highly reproducible and suitable to analyze large numbers of clinical and nonclinical samples. © 2018 The Authors. Cytometry Part A Published by Wiley Periodicals, Inc. on behalf of ISAC. Abstract : The illustration shows a simple, rapid, flow cytometry based assay to measure the capacity of antibodies to mediate Fc‐receptor dependent phagocytosis of labeled bacteria.